Two Alternative Methods to Measure the Radiated Emission in a Reverberation Chamber - Qian Xu; Yi Huang; Sheng Yuan; Lei Xing; Zhihao Tian (International Journal of Antennas and Propagation)
One of the most important applications of a reverberation chamber is for radiated power measurement. Two new alternative methods are proposed to measure the radiated power of equipment under test in a reverberation chamber in this paper. Traditionally, as stated in IEC 61000-4-21 standard, this measurement requires two antennas, a signal generator and a spectrum analyzer or receiver. However, it is found that if a signal generator is not available, a vector network analyzer can be used to complete the measurement. Furthermore, if only one antenna is available, by taking advantage of the enhanced backscattering effect, the measurement can still be completed. By incorporating the one- and/or two-antenna methods, the radiation efficiency of antennas is also considered. Measurements have been conducted to verify the proposed methods, the results from these three methods are compared, and a very good agreement is obtained. It is found that the two proposed methods are simpler than the conventional method.